What is XLIFF and why should I use it? a brief overview of the XML localization interchange file format (XLIFF). - Jewtushenko, Tony
Much time, energy and commitment are required to develop and self successful software products and Web based services. Most products of this type are initially developed for a specific language and locale (e.g. U.S. English). To maximize return on investment, products can be customized so they may be available to the largest possible market-the global market. This customization process is known as localization.